Correlation of lifetime progress of atherosclerosis and morphologic markers of severity in humans: new tools for a more sensitive evaluation (Clinics, 2012)
OBJECTIVES: To describe the morphological features of atherosclerosis in the aortas of autopsied patients (ranging from young adults to the elderly), thus providing new tools for a more sensitive morphological evaluation. METHOD: We collected 141 aorta samples. We assessed the macroscopic degree of atherosclerosis, thickness of the intima and media, lipid and collagen depositions in the intima, and the infiltration of mast cells into the layers of the aorta. We correlated the findings with gender, age, race and cause of death. RESULTS: The degree of atherosclerosis was significantly higher in the elderly. The aorta was thicker in the elderly and in cases with a cardiovascular cause of death. The thickness of the intima was significantly greater in the elderly, in males and in cases with a cardiovascular cause of death. The lipid content in the intima of the aorta was significantly higher in Caucasians. Older people and men had a significantly higher number of mast cells. CONCLUSION: A macroscopic evaluation is a good indicator of the severity of atherosclerosis, but a more detailed analysis, namely evaluating the thickness of the layers of the aorta and the number of mast cells, may further elucidate the changes in the constituents of this vessel.